The Mediating Roles of Mindfulness in Marriage and Mindfulness in Parenting in the Relationship Between Parents' Dispositional Mindfulness and Emotion Regulation of Their Children - Uygun, Ezgi Gueney; Erus, Seher Merve (SPRINGER, 2024)
The fact that primary school is a pre-adolescent period makes it important in terms of regulating emotions. The beginning signals of adolescence occur during this period. It is clear that this challenging process of emotion regulation is linked to age and development, along with parental characteristics and the interactions of the child with the parent. It is believed that researching the variables that influence emotion regulation can help individuals maintain healthy social interactions throughout their journey from childhood to adulthood. In this context, parents' mindfulness levels, which include both intrapersonal and interpersonal processes, play a crucial role in helping their children regulate their emotions. The current study aims to ascertain the serial mediating role of mindfulness in marriage and mindfulness in parenting in the relationship between parents' dispositional mindfulness and the emotion regulation of their children aged 6-10. A total of 333 parents, all of whom were married and had children ranging from 6 to 10 years old, participated in the study. Emotion Regulation Checklist, Mindfulness in Marriage Scale, Mindful Attention Awareness Scale and Mindfulness in Parenting Questionnaire were used in the study. To determine the mediating role, the bootstrap method was used via structural equation modeling (SEM) to ascertain the mediating role. The SEM and bootstrap method revealed that there was a serial mediation effect between parents' dispositional mindfulness and emotion regulation of their children. This effect was attributed to mindfulness in marriage and mindfulness in parenting. Given that the primary school years are a critical developmental stage in improving emotion regulation skills, family-based interventions supporting parents' mindfulness in three important areas (dispositional, marital, and parental) may help to improve the children's capacity to regulate their emotions.
Keywords: Age of 6-10; Emotion regulation; Mindfulness; Mindfulness in marriage; Mindfulness in parenting; ATTENTION AWARENESS SCALE; INTERPERSONAL MINDFULNESS; MARITAL CONFLICT; ADJUSTMENT; PATHWAYS; STRESS; PSYCHOPATHOLOGY; QUESTIONNAIRE; ASSOCIATIONS; VALIDATION; Social Sciences - Other Topics